Evaluation of an Automated Screening Assay, Compared to Indirect Immunofluorescence, an Extractable Nuclear Antigen Assay, and a Line Immunoassay in a Large Cohort of Asian Patients with Antinuclear Antibody-Associated Rheumatoid Diseases: A Multicenter Retrospective Study. (2nd May 2018) - Jeong, Seri; Hwang, Hyunyong; Roh, Juhye; Shim, Jung Eun; Kim, Jinmi; Kim, Geun-Tae; Tag, Hee-Sang; Kim, Hyon-Suk
Abstract : We assessed the diagnostic utility of the connective tissue disease (CTD) screen as an automated screening test, in comparison with the indirect immunofluorescence (IIF), EliA extractable nuclear antigen (ENA), and line immunoassay (LIA) for patients with antinuclear antibody- (ANA-) associated rheumatoid disease (AARD). A total of 1115 serum samples from two university hospitals were assayed using these four autoantibody-based methods. The AARD group consisted of patients with systemic lupus erythematosus (SLE), systemic sclerosis (SSc), Sjögren's syndrome (SS), and mixed connective tissue disease (MCTD). The qualitative results of all four autoantibody assays showed a significant association with AARDs, compared to controls (P < 0.0001 for all). The areas under the receiver operating characteristic curves (ROC-AUCs) of the CTD screen for differentiating total AARDs, SLE, SSc, SS, and MCTD from controls were 0.89, 0.93, 0.73, 0.93, and 0.95, respectively. The ROC-AUCs of combination testing with LIA were slightly higher in patients with AARDs (0.92) than those of CTD screen alone. Multivariate analysis indicated that all four autoantibody assays could independently predict AARDs. CTD screening alone and in combination with IIF, EliA ENA, and LIA are potentially valuable diagnostic approaches for predicting AARDs. Combining CTD screen with LIA might be effective for AARD patients.